Development of communication and sport in China based on mapping of knowledge information visualization - Wei, Y.; Zhang, H.; Yin, H. (SAGE open, 2020)
In China, since the beginning of the 21st century, the study of sports communication has gradually attracted the attention of the academic community, and a number of valuable achievements have emerged. The 2,863 articles that were published by core journals of sport communication from 1982 to 2018 and collected from the CNKI database were chosen as research objects. This article used CitespaceV software to analyze productivity, hot domains, and frontiers in China sport communication research by the methods of bibliometrics method, co-occurrence analysis, and word of frequency analysis. We aimed to grasp the dynamic process of China sport communication research development and provide a valuable reference for its theoretical research and practice. It was shown that first, sport communication researches in China started late but grew fast. Second, the research hotspot of sport communication was related to communication, culture, big data, network, and so on. Third, sport communication research was mainly carried out by universities of sport and communication schools of colleges and universities. Researches were centered around pluralistic, international, and technological aspects with "sport communication" as the focus in drawing experiences from the international sports communication and improve the Chinese sport communication. Rich knowledge and innovative ideas were needed to do the future researches.